2008
DOI: 10.1073/pnas.0805403105
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial strategies in burying beetles breeding on carrion

Abstract: Rich and ephemeral resources, such as carrion, are a source of intense interspecific competition among animal scavengers and microbial decomposers. Janzen [Janzen DH (1977) Am Nat 111:691-713] hypothesized that microbes should be selected to defend such resources by rendering them unpalatable or toxic to animals, and that animals should evolve counterstrategies of avoidance or detoxification. Despite the ubiquity of animal-microbe competition, there are few tests of Janzen's hypothesis, in particular with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
223
6
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(236 citation statements)
references
References 32 publications
6
223
6
1
Order By: Relevance
“…Consequently, there was no difference in the timing of larval dispersal between females breeding on decomposed carcasses and fresh carcasses. The latter result contrasts with a previous study on the same species, 370 which found that dispersal occurred later on decomposed carcasses than on fresh carcasses (Rozen et al 2008). The different results of this previous study may reflect differences in methodology as it used experimental foster broods that were completely synchronous and smaller than our natural broods (Rozen et al 2008), while we allowed females to rear their own broods without interference.…”
contrasting
confidence: 55%
“…Consequently, there was no difference in the timing of larval dispersal between females breeding on decomposed carcasses and fresh carcasses. The latter result contrasts with a previous study on the same species, 370 which found that dispersal occurred later on decomposed carcasses than on fresh carcasses (Rozen et al 2008). The different results of this previous study may reflect differences in methodology as it used experimental foster broods that were completely synchronous and smaller than our natural broods (Rozen et al 2008), while we allowed females to rear their own broods without interference.…”
contrasting
confidence: 55%
“…While adult and larval fruit flies can taste a substrate in order to obtain some information about food quality, taste alone cannot indicate the presence of all essential nutrients. Furthermore, fruit flies are under intense competition with numerous species of fungi and bacteria for feeding on fallen fruit, and many microbes produce secondary compounds that harm other microbes as well as many other animals, including fruit flies (Janzen, 1977;Demain and Fang, 2000;Rohlfs et al, 2005;Rozen et al, 2008). It is thus possible that microbiome volatiles signal to flies the availability of a food substrate with suitable microbial species.…”
Section: Microbiome Volatiles As Salient Cuesmentioning
confidence: 99%
“…This system is particularly interesting for addressing these questions given the peculiar life history of these organisms. Nicrophorus beetles are reared on decomposing carrion where they encounter and ingest high densities of microbes (25)(26)(27)(28)(29). Eggs are laid in the soil near the carcass (25).…”
mentioning
confidence: 99%